Velocity Boundary Layer Analysis of a Flat Plate Heat Exchanger in Laminar Flow: A Case Study - Mirdrikvand, M.; Roozbehani, B.; Moqadam, S. I.; Roshan, A. C.; Ramezani, Y. (Engineering, Technology & Applied Science Research, 2012)
In this article, a behavioral analysis of velocity boundary layer in a flat plate heat exchanger in laminar flow condition through CFD simulation using FLUENT software is done. The main objective of this study is to determine the velocity vectors between the flat plates of the heat exchanger. In addition, wake occurrence, differences of velocity at different surfaces between plates, angles of velocity vectors and the effect of wake phenomenon on the shear stresses exerted on the plates are discussed in detail. The study graphically illustrates results based on fluid’s behavior by a 3D and 2D simulation with air and water as cold and hot streams that affect plate’s situation and its hydro dynamical operations. Consequently, some important design features regarding wake point occurrence and pressure loss are investigated. In addition, eddy current and reverse flows in the wake area and the angles of the velocity vectors are described.